2021
DOI: 10.3389/fcvm.2021.764528
|View full text |Cite|
|
Sign up to set email alerts
|

Malnutrition and Frailty Are Critical Determinants of 6-Month Outcome in Hospitalized Elderly Patients With Heart Failure Harboring Surgically Untreated Functional Mitral Regurgitation

Abstract: Background: Hospitalized patients with acute decompensated heart failure (ADHF) frequently exhibit aggravating mitral regurgitation (MR). Those patients do not always undergo surgical mitral valve repair, but particularly in the elderly, they are often treated by conservative medical therapy. This study was aimed to investigate factors affecting 6-month outcomes in hospitalized patients with heart failure (HF) harboring surgically untreated MR.Methods: We screened the presence of MR in hospitalized patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In the present study, therefore, we used the value of GNRI at discharge. Recent studies ( 42 , 52 ) have shown that GNRI at discharge is a more beneficial indicator of long-term prognosis than assessment at admission, which we believe supports our assessment methodology.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, therefore, we used the value of GNRI at discharge. Recent studies ( 42 , 52 ) have shown that GNRI at discharge is a more beneficial indicator of long-term prognosis than assessment at admission, which we believe supports our assessment methodology.…”
Section: Discussionsupporting
confidence: 80%
“…Although MNA-SF is considered a good indicator for outpatient ( 41 ), it is not suitable for accurate prediction during acute exacerbations of HF since body weight can change quickly due to systemic edema and congestion. In this regard, we expected that GNRI would be a good predictor in hospitalized patients, based on previous reports in hospitalized HFpEF patients and our previous report on its usefulness as a prognostic indicator in VHD patients ( 21 , 42 ). We found that the GNRI predicted all-cause mortality or HF hospitalization one year after discharge with high predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Our work highlights the importance of measuring and evaluating undernutrition, as well as frailty syndrome, as they can predict negative events and an increase in morbidity and mortality. For example, a Japanese study in the context of managing heart failure found that malnutrition and underweight were significant predictors of adverse outcomes in elderly patients with heart failure and surgically untreated moderate-to-severe functional mitral regurgitation [ 23 ]. Frailty syndrome is also characterized by weight loss, a decline in functional abilities and physical strength, and geriatric consequences such as falls, protein-energy malnutrition, and memory problems.…”
Section: Discussionmentioning
confidence: 99%
“…The authors described significantly higher hazards of death (hazard ratio: 3.06; p = 0.001) and death or heart failure decompensation (hazard ratio: 2.03; p = 0.007) in frail patients with severe MR undergoing TMVR compared to non-frail patients. Miura et al [19] found that malnutrition and frailty were predictors for adverse 6-month outcomes in hospitalized patients with heart failure and untreated mitral valve regurgitation and in patients with chronic heart failure (HF), while Yang et al [18] found 1.5-fold higher rates of mortality and incident hospitalization according to the frailty status. However, these results are not surprising, since HF and frailty share common clinical signs and symptoms, such as sarcopenia, cachexia, muscle weakness, reduced cardiac fitness, and increased inflammatory potential [18].…”
Section: Discussionmentioning
confidence: 99%